PENGARUH JENIS MINYAK TERHADAP SIFAT FISIK D AN KIMIA BATH BOMB (THE EFFECT OF THE TYPE OIL ON THE PHYSICAL AND CHEMICAL PROPERTIES OF BATH BOMB) - Annisa Bella Maharani; Lia Destiarti; Nurlina Nurlina; Intan Syahbanu; Winda Rahmalia (Tanjungpura University, 2020)
Bath bombs were produced with ten different types of oil to determine the effect of the oil used on their physical and chemical properties. Bath bombs were prepared by mixing the dry ingredients first (citron, cornstarch, baking soda) and stirring until all the ingredients were well blended. Then, mixed the wet ingredients (water, oil, perfume ore, food coloring) into the beaker. After that, the wet ingredients were poured gradually into the dry dough, and this step was done until all the wet ingredients run out, and the texture of the bath bomb dough was slightly moist so that it can be put in the mold. Finally, the bath bomb is printed and tested in a laboratory. The result showed that the difference in essential oils used in the manufacture of bath bombs does not affect the pH of the bath bomb but affects the stability of the resulting foam. The acceptability test results showed that the resulting bath bomb provided a sensation of freshness and relaxation and did not cause allergies. Based on the SWOT analysis results, these bath bombs can advance and develop by implementing a vertical integration strategy